Furious Frederich: Nietzsche’s neurosyphilis diagnosis and new hypotheses - Charles André; André Rangel Rios (Arquivos de Neuro-Psiquiatria)
The causes of Friedrich Nietzsche’s mental breakdown in early 1889 and of the subsequent slow decay to end-stage dementia along ten years will possibly remain open to debate. The diagnosis of syphilitic dementia paralytica, based only on medical anamnesis and physical examination, was considered indisputable by Otto Binswanger. On the other hand, taking into account recently described diseases, selectively collected evidence lend some support to alternative hypotheses: basal forebrain meningioma, CADASIL, MELAS and frontotemporal dementia.